Dementia as a Current Problem Due to Demographic Trends – Knowledge of Caregivers - Pokorná, Andrea; Dubská, Soňa (University of Pardubice, 2017)
Introduction: Dementia is not a disease but a collection of symptoms resulting from damage to the brain. These symptoms can be caused by a number of conditions. It is generally assumed caregiver’s better knowledge of the symptomatology and symptoms result in a better quality of care. Objective: To assess the knowledge about the causes and symptoms of dementia in a selected sample of family members of seniors with dementia and in non-medical healthcare personnel caring for seniors with dementia at geriatric-psychiatric wards. Method: A questionnaire-based survey applied to a selected group of family members and to non-medical workers (questionnaire by the Institut Universitaire de Gériatrie in Montréal). Results: Younger age lay persons (p = 0.0012) and relatives in a straight line of the elderly showed better knowledge of dementia (p = 0.0002). The relatives’ satisfaction with care did not correlate with their knowledge of the causes and symptoms of dementia (p = 0.5899). The relatives’ gender did not show a statistically significant correlation with knowledge (p = 0.937). However, women showed better knowledge from the objective point of view. In the sample of non-medical professionals, education correlated with the level of proven knowledge of the causes and symptoms of dementia while respondents with university education demonstrated better knowledge (p = 0.0016) as well as respondents with completed specialized education on dementia (p = 0.0003). Family members of seniors with dementia did not give correct answers to questions on the pathophysiology and symptoms related to the progression of dementia. Nonmedical healthcare personnel did not have sufficient knowledge of the general aspects of dementia and some behavioural and psychological symptoms of dementia. Conclusion: The analysis of the family members’ and non-medical healthcare personnel's knowledge about dementia proved statistically significant differences. The knowledge demonstrated by the family members of patients with dementia differs depending on the age and relation to the patient. The level of knowledge demonstrated by non-medical healthcare personnel caring for patients with dementia differs by gender, their achieved level of education and specialized education.
Keywords: care; dementia; family; non-medical personnel; psychiatry